Pemberdayaan Masyarakat melalui Hidroponik dan Pengelolaan Keuangan UMKM Hijau di Kawasan Rawan Banjir Kedaung Kali Angke, Jakarta Barat - Nurul Hidayah; Anton Hindardjo; Fransisca Listyaningsih; Noor Hazlina Ahmad; Anees Jenee Ali (Universitas 17 Agustus 1945 Jakarta, 2026)
This community service program aims to empower residents of Kedaung Kali Angke Subdistrict, West Jakarta, an area facing multiple challenges resulting from high population density, limited land availability, and recurrent flooding. These conditions have adversely affected household food security, increased dependence on external food supply chains, and constrained the capacity of micro, small, and medium enterprises (MSMEs) in financial management and marketing. To address these issues, the program implements an integrated community empowerment model that combines urban hydroponic farming, the development of green MSMEs, and financial literacy enhancement as adaptive strategies for densely populated and flood-prone urban environments. The program is implemented through training, mentoring, and active community participation, focusing on three main components: (1) the adoption of adaptive hydroponic systems to strengthen household food security, (2) basic financial management training for MSMEs, including bookkeeping and cost analysis, and (3) the establishment of community-based green MSME networks to expand marketing opportunities and foster business collaboration. The expected outcomes include improved financial literacy, enhanced household food security, the formation of sustainable green MSME groups, and increased community income. Beyond its direct benefits to the target community, the proposed empowerment model has the potential to serve as a replicable framework for strengthening economic, social, and environmental resilience in other urban areas with similar characteristics.